2018
DOI: 10.1016/j.jobcr.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fracture resistance and mode of failure of premolars restored with nanohybrid composite, ORMOCER and ceramic inlays

Abstract: Based on the present study, the dentist can utilize the ORMOCER material as a restoration material for the cavities of posterior teeth which is better in terms of fracture resistance and durability of the restoration when compare to nanohybrid composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…By replacing a significant portion of the organic resin matrix in traditional composites with these three-dimensional polymeric materials, polymerization shrinkage (1.25% by volume) is reduced. The findings of the present study concur with those of Gunwal et al [42] They examined the fracture resistance, and mode of failure of premolars restored with nanohybrid composite, ormocer, and ceramic inlays. They found that ormocer had the best fracture resistance comparable to natural teeth.…”
Section: Discussionsupporting
confidence: 92%
“…By replacing a significant portion of the organic resin matrix in traditional composites with these three-dimensional polymeric materials, polymerization shrinkage (1.25% by volume) is reduced. The findings of the present study concur with those of Gunwal et al [42] They examined the fracture resistance, and mode of failure of premolars restored with nanohybrid composite, ormocer, and ceramic inlays. They found that ormocer had the best fracture resistance comparable to natural teeth.…”
Section: Discussionsupporting
confidence: 92%
“…Nanohybrid composites on the other hand, have been shown to produce 65% of unfavourable fracture patterns in restored MOD premolar cavities [22]. The unfavourable fractures were suggested to have been the result of resins having poor mechanical properties [22]. The accumulated data of the presented studies concluded that both microhybrid and nanohybrid composites display significant rates of unfavourable fractures.…”
Section: Fracture Patternsmentioning
confidence: 87%
“…Nanohybrid composites on the other hand, have been shown to produce 65% of unfavourable fracture patterns in restored MOD premolar cavities [22]. The unfavourable fractures were suggested to have been the result of resins having poor mechanical properties [22].…”
Section: Fracture Patternsmentioning
confidence: 99%
“…Ormocers are described as three dimensionally cross-linked copolymers [ 30 ] with a polymerization process that does not leave any residual monomer behind, making the ormocers more biocompatible to surrounding tissue [ 31 ]. The obtained results certainly confirm the cariostatic capabilities of ormoceric materials from the Admira group and the concentration levels of fluoride ions released from the surface of these materials can potentially aid in the remineralization of the surrounding tooth tissues.…”
Section: Discussionmentioning
confidence: 99%